AC Biosusceptometry as a Tool for Monitoring the Gastrointestinal Transit of Multiparticulate Drug Delivery System - Oliveira, G. F. [UNESP]; Ferrari, P. C. [UNESP]; Cora, L. A. [UNESP]; Andreis, U. [UNESP]; Miranda, J. R. A. [UNESP]; Evangelista, Raul Cesar [UNESP] (Springer, 2010)
Drug delivery systems based on natural polysaccharides, such as chitosan (CS) and pectin (PC), rather than on synthetic polymers, have been widely studied. Some reasons for that are low toxicity and costs and high biodegradability of the formers. A multiparticulate system based on CS and PC was developed in our laboratories, including the addition of an enteric polymer, cellulose acetate phtalate (CAP). Such improvement promoted stronger gastric and enteric resistances, as assessed in vitro, making the systems more selective to enzymatic degradation in the colon. Although in vitro dissolution tests can simulate some properties concerning the gastrointestinal transit (GT), collaborating to characterize the systems behavior in the biological fluids, frequently they do not result in satisfactory in vitro/in vivo correlations. The objective of this work was to follow in vivo the GT of the particles developed by means of AC biosusceptometry (ACB), a non-invasive and of low cost methodology. The particles containing ferrite in powder form were prepared by complex coacervation using an ideal 3:1:1 mass ratio for PC:CS:CAP. The magnetic particles were administered to healthy volunteers by oral route. The GT was monitored by using multi-sensor ACB system and the signal acquisition was performed every IS min until the colonic region was reached. By means of ACB technique, it was possible to acquiring images generated by the magnetic particles within the whole gastrointestinal tract including the colonic region. Variable particles transit times were observed among the volunteers, but without interference on the mapping of the particles until the colonic region. The particles were able to produce magnetic field strong enough to generate signals adequate for mapping the particles. The results suggest that integral particles reached the colon, after they resisted against gastric and enteric media. Studies associating transit time and in vivo drug release are in development in order to confirm the efficiency of the systems.
Keywords: multiparticulated systems; chitosan; pectin; AC biosusceptometry; colonic delivery systems